Inclusive education: The history and the international experience - Natalia Groznaja (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
This review presents a short history of the international experience in the integration of students with development problems into the general school system. This process is considered in the context of the changes in the attitude to the rights of the people with special educational needs and to their place within society. The author presents statistical data characterizing the situation in different countries in Europe and North America and describes the particular issues of transition to an inclusive education on the example of several countries. The article lists the principal conclusions pertaining to those approaches, that are capable of ensuring the efficiency of education in integrated schools.